Oral and Otorhinolaryngological Findings in Adults Who Were Diagnosed With Pediatric Onset Crohn's Disease: A Controlled Study. Issue 7 (August 2019) - Haaramo, Anu; Alapulli, Heikki; Aine, Liisa; Tuokkola, Jetta; Saarnisto, Ulla; Roine, Risto P.; Pitkäranta, Anne; Kolho, Kaija-Leena
Abstract : Background: Up to 50% of pediatric patients with Crohn's disease (CD) report oral manifestations, but less is known about their oral health when they become adults. Goals: Our aim was to provide detailed descriptions of the presence of oral and otorhinolaryngological manifestations in patients with pediatric onset CD once they reached adulthood, to look for predisposing factors and to compare the findings to matched controls. Study: Adult patients diagnosed with CD in childhood at the Children's Hospital, University of Helsinki, Finland, after 2000 were invited for a follow-up appointment in 2016 and 24 were examined by a dentist and otorhinolaryngologist. They were compared with 22 matched controls from the Population Register Centre. The participants completed questionnaires about their general health, any special diets, and their health-related quality of life. Their nutrition was evaluated from food records. Results: Patients with CD had minor oral manifestations at a median of 9 years after their childhood diagnosis and the most common was angular cheilitis, which affected 6 patients and 1 control, but was not statistically significant ( P =0.0984). CD with perianal abscessing disease correlated to orofacial findings ( P =0.0312). Most of the patients had normal otorhinolaryngological findings. Subjects with oral lesions had lower mean health-related quality of life scores than subjects without oral findings and the differences were clinically but not statistically significant. Oral manifestations were not associated with differences in energy intake. Conclusions: Oral manifestations in adult patients with pediatric onset CD were mild and were not associated with otorhinolaryngological pathology. Abstract : Supplemental Digital Content is available in the text.